Shams et Toghrā. figures romanesques de l'Iran mongol - Christophe Balaÿ (Revue des Mondes Musulmans et de la Méditerranée)
In this article, the author tries to show how, through the historical novel genre which appears in Iran at the beginning of the 20th century, Mohammad Bâqer Khosravi presents a new romance approach of the Iranian history.